2022
DOI: 10.3390/nano12234134
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Ultraviolet Lighting Using Carbon Nanotube-Based Cold Cathode Electron Beam

Abstract: Laser-based plasma studies that apply photons to extreme ultraviolet (EUV) generation are actively being conducted, and studies by direct electron irradiation on Sn for EUV lighting have rarely been attempted. Here, we demonstrate a novel method of EUV generation by irradiating Sn with electrons emitted from a carbon nanotube (CNT)-based cold cathode electron beam (C-beam). Unlike a single laser source, electrons emitted from about 12,700 CNT emitters irradiated the Sn surface to generate EUV and control its i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…When I photo is 4 μA, the usable time without melting Sn is 506 s. Additionally, in our previous study, it was confirmed that a PMMA photoresist that reacts to an EUV dose of 25 mJ cm −2 can be sufficiently reacted with C-beam based EUV light with I photo of 4 μA in 30 s of exposure. 24,32) When irradiating one C-beam, the usable time without melting Sn and I photo are in a trade-off relationship. The usage time is shorter to use enhanced EUV lighting.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When I photo is 4 μA, the usable time without melting Sn is 506 s. Additionally, in our previous study, it was confirmed that a PMMA photoresist that reacts to an EUV dose of 25 mJ cm −2 can be sufficiently reacted with C-beam based EUV light with I photo of 4 μA in 30 s of exposure. 24,32) When irradiating one C-beam, the usable time without melting Sn and I photo are in a trade-off relationship. The usage time is shorter to use enhanced EUV lighting.…”
Section: Resultsmentioning
confidence: 99%
“…The intensity of EUV light generated by the C-beam varies with anode voltage and electron incident angle as well as anode current. 24) Sn has a low melting point of about 232 °C, so it cannot withstand high-energy electron bombardment. EUV intensity increases in proportion to the electron impact power of the C-beam, 24) but as Sn melts, vaporized Sn particles act as debris and can contaminate the inside of the EUV system.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We believe that this high-efficiency, long-term stable cathode has great potential for using in neutralizers, solar sails and tethered satellites in the long-term space missions.Carbon nanotubes (CNTs) present numerous advantages as the field emission cathodes (FEC), such as its ultralow turn on voltage (>0.4 V/μm) 1, 2 resulting from the low work function (~5 eV), [3][4][5] exceptional chemical and physical stabilities, 6 as well as high electrical and thermal conductivity 7, 8 attributed to the C-C covalent bond, seamless hexagonal network architecture and one-dimension carbon nanostructures. 9, 10 These unique characteristics render FEC an ideal electron source for various applications, including field emission scanning electron microscopy (FESEM), 11 field emission display (FED), 12 electron-beam (E-beam) lithography (EBL) 13,14 and X-ray tube. 15 In modern space technologies, 16,17 FEC often severs as the cathode for electric propulsion (EP) system, providing electrons to neutralize the positive ions or positively charged droplets to avoid charging of the spacecraft.…”
mentioning
confidence: 99%